Evaluating Alcohol Use among Russian Women at Risk for an Alcohol-Exposed Pregnancy: A Comparison of Three Measures of Alcohol Use - Balachova, Tatiana (J Ethn Subst Abuse, 2016)
The Quick Drinking Screen (QDS) and Timeline Followback (TLFB), measures of alcohol use, have yielded similar reports of drinking with English speakers. The present study, a secondary data analyses, compared three measures of alcohol use (i.e., QDS, TLFB, and AUDIT) with Russian-speaking women. This is the first study to compare all three measures. This study replicated the findings of studies with English speakers, and demonstrated that brief screening measures (QDS, AUDIT) provide reliable summary measures of alcohol use when compared to a detailed drinking measure (TLFB). The use of brief screening measures is recommended for use with Russian women.